2019
DOI: 10.1093/nar/gkz492
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient silencing of microRNA by heteroduplex oligonucleotides

Abstract: AntimiR is an antisense oligonucleotide that has been developed to silence microRNA (miRNA) for the treatment of intractable diseases. Enhancement of its in vivo efficacy and improvement of its toxicity are highly desirable but remain challenging. We here design heteroduplex oligonucleotide (HDO)-antimiR as a new technology comprising an antimiR and its complementary RNA. HDO-antimiR binds targeted miRNA in vivo more efficiently by 12-fold than the parent single-stranded antimiR. HDO-antimiR also produced enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…The Toc-HDO (coRNA) design significantly enhanced the antisense potency of the parent ASO in mouse liver. [13][14][15][16][17] We also showed that the coRNA of the Toc-HDO (coRNA) is stable in the serum and that conjugation with Toc enhances productive delivery to the liver by enhancing association with serum lipoproteins. Toc-HDO (coRNA) was taken up into cells mostly in the intact form, after which the coRNA strand was cleaved by RNase H with the release of the parent ASO inside the cells.…”
Section: Introductionmentioning
confidence: 92%
“…The Toc-HDO (coRNA) design significantly enhanced the antisense potency of the parent ASO in mouse liver. [13][14][15][16][17] We also showed that the coRNA of the Toc-HDO (coRNA) is stable in the serum and that conjugation with Toc enhances productive delivery to the liver by enhancing association with serum lipoproteins. Toc-HDO (coRNA) was taken up into cells mostly in the intact form, after which the coRNA strand was cleaved by RNase H with the release of the parent ASO inside the cells.…”
Section: Introductionmentioning
confidence: 92%
“… 5 MicroRNA-targeting HDO (HDO-antimiR) displayed high potency in cleaving the target microRNA, whereas the parental ASO exerted its potency via a steric blocking (not cleaving) mechanism. 6 Additionally, HDO-antimiR conjugated with GalNAc was more potent in the liver than the parent ASO conjugated with GalNAc, where delivery efficiency of HDO was comparable to that of ASO. 6 These findings suggested that HDO may have a distinct intracellular trafficking pathway and processing machinery different from the single-stranded ASO.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Additionally, HDO-antimiR conjugated with GalNAc was more potent in the liver than the parent ASO conjugated with GalNAc, where delivery efficiency of HDO was comparable to that of ASO. 6 These findings suggested that HDO may have a distinct intracellular trafficking pathway and processing machinery different from the single-stranded ASO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have established the utilization of ASOs for the targeting of microRNAs, and ultimately an efficient approach to enhance protein production (Fig. 1 ) [ 65 , 79 , 91 , 92 ]. The microRNAs (short RNAs consisting of 21-23 nucleotides) inhibit the gene expression or protein translation and control associated gene networks.…”
Section: Introductionmentioning
confidence: 99%